Recognition and rating of effecting indexes on consumption of different sites poplar wood production in Iran for paper making industries - ebrahim lashkarbolouki; kambiz pourtahmasi; reza oladi; mohsen kalagari; hasan alizadeh (Iranian Journal of Wood and Paper Industries, 2016)
Considering the growth in population, the need for wood consumption also increases. The rapid progress of science and technology doubles the wood consumption. Supplying this need at a glance was focused on the forests. Forests for many reasons have faced decrease in production and this extreme need for wood, by planting fast growing trees (poplar, eucalypt, Paulownia …) makes it possible. One of industries plenty of the wood is paper industry that needs to huge primary wood material. This industry can continue their production activities by using the wood of poplar. This research was found out with the aim of assessing the practical characteristics of poplar wood by nondestructive test method in paper production industry. Poplar sites were selected in areas of country that poplar trees were planted widely. For locating the production of different site in paper industry found out Analytic Hierarchy Process (AHP) in Expert choice 11 software. For field studies of this research, the questionnaires were prepared and sent for expert and university professors with special expertise in this industry. The results showed that: Production of Pulp and paper industry: in this industry among of five main indexes influencing in pulp and paper production, fiber morphology trait recognized as first priority with weighting value (0.435). Production allocations with their weighting value are determined: Sari (0.240), Fouman (0.236), Lashtnasha (0.182), Abhar (0.174) and Zanjan (0.168), respectively.